Dedicated to the Great Victory - Harunova, Marianna M.-B. (The New Research of Tuva, 2010)
Article represents an overview of the round table "The victory of Soviet people over the Nazi Germany is a victory of Tuvan people as well", that was held on April 30, 2010 in the Tuvan Institute of Humanitarian Researches.